Reflective Approach Towards Professional Teacher Education – Inspiration Experiences, Questions - Tomková, Anna (Wydawnictwo Naukowe UAM, 2013)
The topic of the paper is the reflective approach towards professional teacher education. Its goal is to consider the relationship between teacher education and definition of the quality of teacher performance as well as the relationship between teacher education and means of professional competence evaluation. Another aim is to introduce core principles and selected examples of reflective approach to primary school teacher education at the Faculty of Education of Charles University in Prague. The paper will present reflected examples of specific procedures used in pedagogical and psychological classes, in the course of teaching practice and during optional courses.
Refleksyjne podejście w kształceniu zawodowym nauczycieli – inspiracje, doświadczenia, pytania
Keywords: professional education; reflective approach; reflection and self-reflection; reflection; double-entry diary; description of pedagogical situations; portfolio